THE DIGITAL LITERACY AS EDUCATIONAL TOOL FOR DEVELOPMENT OF FITNESS CARDIORESPIRATORY (Fiep Bulletin - online, 2016)
This study aims to identify the improvement of cardiorespiratory fitness and the benefits of fitness for practicing using as a pedagogical tool for this made the digital literacy. The research is bibliographical and quantitative field. Study participants were 41 schoolchildren of both sexes enrolled in the 6th year of elementary school of Mr. Deputy Lauro Carneiro de Loyola in Joinville/SC, for the study were used lesson plans with stretching exercises and running with gradual increase every month and often two to three times a week, digital camera to photograph and film classes and evaluation sheets. The pre- and post-test were developed according to the Klissouras protocol (modified by Matsudo). The children were assessed and reassessed within 5 months. The results showed the difference between the pre- and post-test, where after the exposure period, some obtained an evolution and other involution. Through statistical analysis according to the Student t test, the intervention achieve significant improvements because (p
Keywords: Digital Literacy; Physical Education and Health; Cardiorespiratory Fitness